Antibiotic prescribing for upper respiratory tract infections in the Asia-Pacific region: A brief review - Teng, CL (Malays Fam Physician, 2014)
This review highlights the high prevalence of antibiotic use for upper respiratory tract infections (URTIs) in a larger part of the Asia-Pacific region. Since URTIs are one of the common reasons for primary care consultations in this region, inappropriate use of antibiotic in both quantity and drug choice has greatly influenced the development of antibiotic resistance. Notwithstanding the paucity of Asia-Pacific data on the above issues, the available information suggests urgent actions needed to be taken to promote judicious antibiotic use at the point-of-care through a multi-pronged approach targeting the patients/consumers (or parents), healthcare providers and health care systems.